2010
DOI: 10.1210/er.2010-0004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelet-Derived Growth Factors in the Testis

Abstract: Normal development and function of the testis are controlled by endocrine and paracrine signaling pathways. Platelet-derived growth factors (PDGFs) are growth factors that mediate epithelial-mesenchymal interactions in various tissues during normal and abnormal processes such as embryo development, wound healing, tissue fibrosis, vascular disorders, and cancer. PDGFs and their receptors (PDGFRs) have emerged as key players in the regulation of embryonic and postnatal development of the male gonad. Cells that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 175 publications
(248 reference statements)
2
51
0
1
Order By: Relevance
“…Previous studies indicated that DHH and PDGF are involved in the normal development of the fetal and adult Leydig cell populations (25,26,(29)(30)(31)(32). The specific roles of these factors in the functions of stem Leydig cells in adult testes were not elucidated.…”
Section: Lh -+ ----+ ----+ ---Dbcamp--+ ----+ ----+ --22hc ---+ ----+mentioning
confidence: 99%
“…Previous studies indicated that DHH and PDGF are involved in the normal development of the fetal and adult Leydig cell populations (25,26,(29)(30)(31)(32). The specific roles of these factors in the functions of stem Leydig cells in adult testes were not elucidated.…”
Section: Lh -+ ----+ ----+ ---Dbcamp--+ ----+ ----+ --22hc ---+ ----+mentioning
confidence: 99%
“…Transcripts of rat Pdgfrb are detected at embryonic day 18 (E18), reach high levels on 5 dpn, and then decline to lower levels [72]. Pdgfr can activate gonocytes to migrate from the central region of the seminiferous tubule to the basal lamina of the seminiferous epithelium and initiate their differentiation to spermatogonial stem cells [73], which suggests that gene transcription of the MAPK pathway in the spermatogenic cells should be more active in PN1. Moreover, Sertoli cells in PN2 are nearly mature, which makes the MAPK pathway activated by FSH repressive.…”
Section: Differential Expression Of Genes In Cellular Signaling Pathwaysmentioning
confidence: 99%
“…We analyzed differentially expressed genes related to male reproductive function using GO analysis. In total, eight differentially expressed genes were found in newborn mice of the ICSI group, among which Amh and Rhox5 are expressed in Sertoli cells (Hu et al, 2007;Goulis et al, 2008), Adcy1p1r1 and Pdgfra are expressed in Leydig cells (Koh and Won, 2006;Basciani et al, 2010), while the other four genes are mainly expressed in spermatocytes (Lee et al, 2002;Abreu et al, 2010;Bellani et al, 2010;Puverel et al, 2011). There are two essential stages for testicle development: embryonic and pubertal age.…”
Section: Discussionmentioning
confidence: 99%
“…PDGFRA is essential for early embryonic development of Leydig cells (Basciani et al, 2010). Testosterone is produced by the Leydig cells.…”
Section: Discussionmentioning
confidence: 99%